2018
DOI: 10.1111/1758-2229.12620
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of σ factors by conserved partner switches controlled by divergent signalling systems

Abstract: Partner-Switching Systems (PSS) are widespread regulatory systems, each comprising a kinase-anti-σ, a phosphorylatable anti-σ antagonist and a phosphatase module. The anti-σ domain quickly sequesters or delivers the target σ factor according to the phosphorylation state of the anti-σ antagonist induced by environmental signals. The PSS components are proteins alone or merged to other domains probably to adapt to the input signals. PSS are involved in major cellular processes including stress response, sporulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 123 publications
0
10
0
Order By: Relevance
“…Western blotting analysis revealed that the WT and mutant forms of RsfB were expressed at similar levels in the M. smegmatis strains used in the experiment. These results suggest the followings: (i) unphosphorylated RsfB is the active form of RsfB as an anti-SigF antagonist, (ii) phosphorylation of RsfB on Ser-63 decreases the functionality of RsfB as in the RsfB homologs such as RsbV and SpoIIAA of B. subtilis (Bouillet et al, 2018), (iii) Thr-32 is important for anti-SigF antagonist activity of RsfB.…”
Section: The Functionality Of Rsfb Is Controlled Through Phosphorylatmentioning
confidence: 85%
See 2 more Smart Citations
“…Western blotting analysis revealed that the WT and mutant forms of RsfB were expressed at similar levels in the M. smegmatis strains used in the experiment. These results suggest the followings: (i) unphosphorylated RsfB is the active form of RsfB as an anti-SigF antagonist, (ii) phosphorylation of RsfB on Ser-63 decreases the functionality of RsfB as in the RsfB homologs such as RsbV and SpoIIAA of B. subtilis (Bouillet et al, 2018), (iii) Thr-32 is important for anti-SigF antagonist activity of RsfB.…”
Section: The Functionality Of Rsfb Is Controlled Through Phosphorylatmentioning
confidence: 85%
“…SigF belongs to group III sigma factors and is dispensable for growth of M. tuberculosis and M. smegmatis (Chen et al, 2000;Williams et al, 2007;Provvedi et al, 2008;Singh et al, 2015). SigF is phylogenetically and functionally in close relation to the well-studied stress sigma factor SigB in Bacillus species (DeMaio et al, 1996(DeMaio et al, , 1997Hecker and Volker, 2001;Hecker et al, 2007;Bouillet et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two other Che systems of S. oneidensis are not involved in chemotaxis control. Indeed, one is probably non‐functional due to an IS insertion in the corresponding cheA gene (Che2), while the other controls a partner‐switch system involved in σ S sequestration/release (Che1) (Armitano et al ., ; Bouillet et al ., , ).…”
Section: Introductionmentioning
confidence: 99%
“…PSS that regulate other traits have been described in diverse bacteria, such as biofilm formation in Vibrio fischeri (Morris and Visick, 2010), type III secretion system in Bordetella (Mattoo et al, 2004), biofilm formation and motility in Pseudomonas aeruginosa (Bordi et al, 2010;Bhuwan et al, 2012) or hormogonium development in Nostoc punctiforme (Riley et al, 2018). Proteins containing specific domains are shared by all these systems: a C-terminal phosphatase 2C (PP2C phosphatase) like in RsbU, an ATPase/kinase domain (GHKL domain) like in RsbW and a sulfate transporter and anti-sigma factor antagonist (STAS) domain protein like in RsbV (Sharma et al, 2011;Bouillet et al, 2018). In some cases like in V. fischeri and Bordetella, the target proteins of the PSS are not yet identified (Kozak et al, 2005;Thompson and Visick, 2015).…”
Section: Introductionmentioning
confidence: 99%